PENTINGKAH KETERAMPILAN POLITIK ORGANISASI, SAAT TIDAK ADA PERBEDAAN PADA KUALITAS HUBUNGAN PEMIMPIN-BAWAHAN? - Kabul Wahyu Utomo (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This study tries to focus on testing about political skills as moderating variable to the relationship between demographic similarity especially ethnic and the quality of leader-member exchange. This study used the survey method and using by questionnaires. From the questionnaire spread as many as 500, the number of questionnaire can be processed are 364 (the respond rate 72,8 % ). The research is done in four institutions in two cities in Jakarta and Yogyakarta. Variables in this study were variable independent used of similarity ethnic between leaders and subordinate. Their dependent variable is the quality of leader-member exchange. Next, the relationship between the two the variable is moderated by political skill as moderating variable. The analysis was conducted using regression analysis and the hierarchical regression. The outcome of this study suggests that there is a positive correlation between the demographic similarity of superior-subordinate specialty ethnicity and the quality of leader-member exchange. Then, the interesting thing about the research is correlation between the demographic similarity of superior-subordinate specialty ethnicity and the leader-member exchange moderated by political skills. But there is an interesting one, that is the connection between a demographic similarity (ethic) and the leader-member exchange moderated by the political skills has negative effect. Furthermore, discussion, the implications and many recommendation of this study are discussed in this study.